Mendoncia amabilis (Acanthaceae), a remarkable new species from the Amazon basin - Silva, Fabio Araújo Da; Kameyama, Cíntia; Betancur, Julio; Zappi, Daniela C. (Phytotaxa, 2023)
A new species, Mendoncia amabilis, is described from the Amazonia as part of an ongoing taxonomic revision of the genus for the Neotropical region. The new species was found from Colombian and Peruvian Amazonia, occurring at river margins below 100 m. It is easily recognized by its strigose petiole, leaf-blades sparsely strigose to glabrescent beneath, broad membranous bracteoles, hirsute calyx, and sericeous ovary. Taxonomic comments, illustrations and SEM images of vegetative and reproductive features, a distribution map, and a conservation assessment are provided.